Predictive value of systemic and local inflammation parameters in talc pleurodesis assessment - Habal, Petr; Omran, Nedal; Jankovicova, Karolina; Krejsek, Jan; Mandak, Jiri (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2015)
BACKGROUND: One option for the palliative treatment of recurrent malignant pleural effusion is powdered talc using thoracoscopy. This paper presents the results of selected systemic and local manifestations of the talc-induced inflammatory reaction using a videothoracoscope. METHOD: A total of 114 patients with repeated malignant pleural effusion were treated at the Cardiac Surgery Clinic in Hradec Kralove from January 2010 to December 2012. Those with a life expectancy more than ≥ 3 months were eligible for talcage surgery. The group was retrospectively divided according to treatment results into Group A (N1 = 98 - successful) and Group B (N2 = 16 - relapsing). The pleural effusion was quantified using ultrasound over 1 year at 3-month intervals. Systemic changes due to the inflammatory reaction (body temperature, serum leukocyte and CRP levels) were evaluated. Local indicators of inflammation included changes in the leukocyte cell population in the effusion and changes in the pleural CRP levels. The dynamics of local expression of membrane receptors TLR-2 and CD-64 on granulocyte and monocyte cell populations in the pleural effusion were also evaluated. RESULTS: The reaction after talcage, included a significant increase in axillary temperature and leukocyte count, 12 h after the procedure. The dynamics were different in the two groups. The dynamics of local inflammatory changes were an early increase in the pleural CRP levels in both groups. The time interval of local inflammatory development and duration was related to the treatment efficacy and showed a significant rise 2 h after talcage in Group A. In Group B the local inflammatory reaction was slower and the rise was only observed 24 h after talc application. A decrease in lymphocyte count and an increase in granulocyte count 2 h after talcage were found. After an initial drop in monocyte level, a rise occurred within 24 h after talcage. Changes in the expression of TLR-2 and CD-64 receptors in relation to their cell carriers were observed depending on time after talcage. CONCLUSION: The differences in the serum and pleural effusion CRP levels suggest that the surgical stress manifests itself locally in the pleural space with a lower intensity and time delay. The TLR-2 and CD-64 receptors exhibit different behaviour depending on the type of cell membrane where they are found. The inverse relation between the granulocyte increase and TLR-2 receptor decrease in the membrane immediately after talcage is a new finding. The dynamics of TLR-2 expression on the monocytes demonstrates a direct proportion between the increasing expression of the TLR-2 receptor and increasing percent fraction of the cell carrier.
Keywords: pleuritida; délka pobytu; Body Temperature; Ultrasonography; thoracoscopy; Lymphoma; Aged; lymfom; Treatment Outcome; CD-64; Recurrence; Retrospective Studies; paliativní péče; lidé středního věku; nádory plic; maligní mezoteliom; senioři; metastázy nádorů; Thoracoscopy; ultrasonografie; torakoskopie; C-reaktivní protein; recidiva; malignant pleural effusion; lidé; Leukocytes; Mesothelioma, Malignant; Middle Aged; Pleurisy; maligní pleurální výpotek; Pleurodesis; mezoteliom; Palliative Care; mastek; Talc; Pleural Effusion, Malignant; pleurodéza; Female; tělesná teplota; Predictive Value of Tests; Lung Neoplasms; CRP; výsledek terapie; TLR-2; talc; Male; ženské pohlaví; C-Reactive Protein; Humans; mužské pohlaví; Length of Stay; prediktivní hodnota testů; Neoplasm Metastasis; leukocyty; Mesothelioma; retrospektivní studie